1986
DOI: 10.1111/j.1365-2672.1986.tb04301.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of the heat resistance of Salmonella typhimurium by sublethal heat shock

Abstract: The survival of Salmonella typhimurium after a standard heat challenge at 55 degrees C for 25 min increased by several orders of magnitude when cells grown at 37 degrees C were pre-incubated at 42 degrees, 45 degrees or 48 degrees C before heating at the higher temperature. Heat resistance increased rapidly after the temperature shift, reaching near maximum levels within 30 min. Elevated heat resistance persisted for at least 10 h. Pre-incubation of cells at 48 degrees C for 30 min increased their resistance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
99
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(108 citation statements)
references
References 23 publications
8
99
0
Order By: Relevance
“…The amount of the enzyme formed after the temperature down-shift depended on the length of incubation at the increased temperature. It reached the maximum value when the population was incubated for 2 h at 45 "C before being transferred to 35 "C. This is in accordance with the idea that the early sporulation phases were slowed down at 43.5 "C or inhibited at 45 "C and resumed at 35 "C. The unfavourable effect of high temperatures on the viability of prokaryotic and eukaryotic cells can often be reduced by their previous exposure to a slightly supraoptimal temperature (Mackey & Derrick, 1986;Carper et al, 1987). We therefore followed the effect of the previous exposure to a temperature of 42 or 45 "C during growth on the subsequent sporulation at 43.5 "C, a temperature that was normally non-permissive.…”
Section: Resultssupporting
confidence: 70%
“…The amount of the enzyme formed after the temperature down-shift depended on the length of incubation at the increased temperature. It reached the maximum value when the population was incubated for 2 h at 45 "C before being transferred to 35 "C. This is in accordance with the idea that the early sporulation phases were slowed down at 43.5 "C or inhibited at 45 "C and resumed at 35 "C. The unfavourable effect of high temperatures on the viability of prokaryotic and eukaryotic cells can often be reduced by their previous exposure to a slightly supraoptimal temperature (Mackey & Derrick, 1986;Carper et al, 1987). We therefore followed the effect of the previous exposure to a temperature of 42 or 45 "C during growth on the subsequent sporulation at 43.5 "C, a temperature that was normally non-permissive.…”
Section: Resultssupporting
confidence: 70%
“…Greater heat resistance by a prior exposure to a sublethal heat stress has been reported for E. coli (14) and other gramnegative (11,12) and gram-positive (3) bacteria. In Salmonella enterica serovar Typhimurium, this elevated heat resistance was shown to persist for at least 10 h of exposure at preincubation temperatures of 42, 45, and 48°C for cells in a stationary phase (11).…”
Section: Efficacy Of the Elisa Technique Developed To Quantify Dnakmentioning
confidence: 99%
“…It was elaborated before the discovery of bacterial sensitivity and resistance and/or adaptation to stress, in particular heat stress. In several species, prior exposure to a sublethal heat treatment was shown to increase bacterial resistance to a subsequent and severer treatment (3,11,12,14), and this knowledge challenges the predictions of classical bacteriology during heating at lowto-moderate temperatures (50 to 65°C).…”
mentioning
confidence: 99%
“…Inactivation time also varies according to the food matrices and their heat transfer characteristics (2)(3)(4). In addition, the bacteria, which have already experienced a sublethal heat shock, become more resistant to further treatment at elevated temperatures (5)(6)(7). Recent studies have reported that some Escherichia coli strains can still grow above 65°C (3) and can survive in ground beef after a cooking period to the recommended internal temperature of 71°C (8).…”
mentioning
confidence: 99%